ROLE OF PROBIOTICS IN SUSTAINABLE SHRIMP FARMING ALONG BALASORE COAST, ORISSA - DURGA PRASAD BEHERA,; LAKSHMAN NAYAK, (The Bioscan, 2011)
The present study has been undertaken to know the role of probiotics in sustainable shrimp farming along the coastal Balasore of Orissa. The hydrological parameters like water temperature, pH, salinity, transparency and alkalinity were observed weekly where as hardness was observed every 20 days of culture (DOC) for a period of six month and dissolved oxygen was observed every day in the early morning and evening throughout the culture beginning from 30 days of culture. The highest water temperature was observed to be 30.3ºC and the lowest was 25.33ºC. The highest water pH was observed be 8.53 and the lowest was 7.26. The highest salinity was observed to be 24.66 ppm and lowest was 11.66 ppm. The highest transparency was observed to be 43 cm and lowest was 17 cm. Likewise, the highest carbonate was observed to be 57.33 ppm and lowest was 11.33 ppm. The highest bicarbonate alkalinity was observed being 285 ppm and lowest was 100 ppm. The hardness varied from 8443 ppm to 3533 ppm. The highest and lowest dissolved oxygen was observed to be 4.53 ppm and 3.53 ppm during culture period. Five different commercial brands of Probiotics of unique composition were used for different ponds during every month. Though bacterial load present inside the culture ponds throughout the culture period it does not show any problem due to application of probiotics which helped for suppression and maintaining of a clean and hygienic environment for sustainable shrimp culture.